2015
DOI: 10.1142/s0218301315300118
|View full text |Cite
|
Sign up to set email alerts
|

Early thermalization, hydrodynamics and energy loss in AdS/CFT

Abstract: Gauge/gravity duality has provided unprecedented opportunities to study dynamics in certain strongly coupled gauge theories. This review aims to highlight several applications to heavy ion collisions including far-from-equilibrium dynamics, hydrodynamics and jet energy loss at strong coupling.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 111 publications
(182 reference statements)
4
46
0
1
Order By: Relevance
“…Very similar results should be obtained in different pictures of heavy ion collisions, even though the language is rather different [29][30][31]. We found that the baryon densities in the fireballs outside the central rapidity region attain values an order of magnitude greater than normal nuclear matter.…”
supporting
confidence: 82%
“…Very similar results should be obtained in different pictures of heavy ion collisions, even though the language is rather different [29][30][31]. We found that the baryon densities in the fireballs outside the central rapidity region attain values an order of magnitude greater than normal nuclear matter.…”
supporting
confidence: 82%
“…First, most of the energy of the incoming projectiles is deposited into a long-lived, quasistatic blob of energy at mid-rapidity. This in contrast to collisions in theories without phase transitions [2][3][4][5][6][7][8][9][10], where the energy density profile after the collision exhibits a minimum at mid-rapidity and two maxima away from mid-rapidity. Second, the physics of the collision is qualitatively identical for the three values of φ M shown in Fig.…”
mentioning
confidence: 86%
“…[1] for a review). The first examples [2][3][4][5][6][7][8] considered gravity models dual to conformal field theories (CFTs). These studies were subsequently extended to non-conformal theories in [9,10] based on the set of models introduced in [11].…”
mentioning
confidence: 99%
“…Issues of thermalization have recently received renewed attention, due in part to numerous experiments probing quantum dynamics in approximately closed systems [5][6][7][8][9][10][11][12] as well as new theoretical tools, like AdS=CFT duality, which are able to address dynamics in isolated strongly interaction systems (see Refs. [13,14] for a review). In general, there are numerous time scales associated with thermalization, which proceeds through distinct stages.…”
Section: Introductionmentioning
confidence: 99%